Optimal site for applying transcutaneous bilirubinometer as an outpatient screening tool for neonatal jaundice: a comparison between the sternum and forehead - Zhang, Emily; Wu, Tzong-Jin; Hudak, Mark L.; Yan, Ke; Teng, Ru-Jeng (Frontiers in Pediatrics, 2024)
Background The gold standard for assessing neonatal jaundice (NJ) is the serum total serum bilirubin (TSB) level by the diazo method. A transcutaneous bilirubinometer (TCB) provides a convenient, noninvasive readout within minutes. The reliability of TCB as the diagnostic tool and the proper site for TCB measurement remains unsettled. Objectives This study aimed to (1) evaluate the reliability of TCB in the NJ outpatient management and (2) identify a better site to obtain TCB readings. Methods This retrospective study examines data collected prospectively over 15 months at a level III facility. Parents were advised to bring their neonates back to our nursery if neonates were judged to be at risk for NJ or poor weight gain, and a follow-up with the primary practitioner was not available. Those who had received phototherapy or sustained forehead bruising were excluded from the analysis. Blood was collected immediately after TCB readings for TSB measurement using the di-azo method. The primary endpoint was admission for treatment according to the AAP 2004 guidelines. A mixed-effects model was used to assess the correlation of forehead TCB (TCB-f) or sternal TCB (TCB-s) with TSB by adjusting for age at measurement (hours), gestational age (GA), sex, and race. Repeated Measure Receiver Operator Characteristic (ROC) curves were constructed for TCB readings against the hospital admission, and the cutoffs for each method were selected to balance the sensitivity and specificity. Results There were 500 visits for 350 neonates, including 136 females, 114 white, 134 black, 71 Hispanic, and 30 Asian. The mean GA was 38.5 weeks [standard deviation (SD) = 1.6], and the mean body weight (BW) was 3,238 g (SD = 506). Forty-five (12.9%) neonates were admitted for phototherapy or blood exchange transfusion according to the TSB levels. Only 43 admitted neonates had all three measurements. Assuming TCB has the same reading as TSB, 30 out of 43 (69.8%) and 20 out of 43 (46.5%) neonates would be sent home if only TCB-f and TCB-s were used, respectively. TCBf has a trend of underestimating the necessity of hospitalization compared to TCBs (p = 0.092 by McNemar test). After adjusting for age of measurement, GA, sex, and race, both TCB-f and TCB-s readings positively correlated with TSB (p < 0.0001). Using repeated measure ROC, with hospital admission for treatment as the primary outcome, the area under the curve (AUC) for TCB-f was 0.79 (95% CI: 0.71–0.86), and AUC for TCB-s was 0.86 (95% CI: 0.81–0.92). A cutoff of 14.3 for TCB-s gave a sensitivity of 81% and a specificity of 78%. A cutoff of 12.6 for TCB-f gave a sensitivity of 80% and a specificity of 65%. Conclusions TCB measurements can discriminate well in predicting admission for NJ treatment in our nursery but tend to underestimate the severity. The sternum is a better site for TCB measurements. We must point out that more than 40% of neonates who should be admitted for NJ management would be sent home if TSB were not obtained simultaneously. We recommend adjusting TCB readings according to unit-based calibration before clinical implementation.